2016
DOI: 10.1093/mnras/stw2977
|View full text |Cite
|
Sign up to set email alerts
|

Long-term variability of T Tauri stars using WASP

Abstract: We present a reference study of the long-term optical variability of young stars using data from the WASP project. Our primary sample is a group of well-studied classical T Tauri stars (CTTS), mostly in Taurus-Auriga. WASP lightcurves cover timescales up to 7 years and typically contain 10000-30000 datapoints. We quantify the variability as function of timescale using the time-dependent standard deviation 'pooled sigma'. We find that the overwhelming majority of CTTS has low-level variability with σ < 0.3 mag … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 86 publications
1
34
0
Order By: Relevance
“…Bozhinova et al 2016) or irregular accretion (e.g. Bouvier et al 2004;Rigon et al 2017), we tested similar hypotheses in our type II and III models, respectively. Accretion variability has also been predicted in magnetohydrodynamics simulations of forming planets (e.g.…”
Section: Discussionmentioning
confidence: 80%
“…Bozhinova et al 2016) or irregular accretion (e.g. Bouvier et al 2004;Rigon et al 2017), we tested similar hypotheses in our type II and III models, respectively. Accretion variability has also been predicted in magnetohydrodynamics simulations of forming planets (e.g.…”
Section: Discussionmentioning
confidence: 80%
“…These flux increases happen on a timescale of decades to centuries. The authors note that although the continuum flux increases are smaller than observed in classical FUOrs, the variability found in their models is larger than currently observed for non-eruptive young protostars (Rebull et al 2015;Flaherty et al 2016;Rigon et al 2017). The variability of their models is also larger than that found by the TRANSIENT Survey (Mairs et al 2017;Johnstone et al 2018;Mairs et al 2018), which reports secular changes of order 5-10% per year from about 10% of the protostars bright enough to get good measurements.…”
Section: Introductionmentioning
confidence: 79%
“…Similarly Grankin et al (2007) find that 20 percent of their sample of Class II objects show significant variability on a timescale of years, in much the same way as we find a third of our Class II sample are in our longtimescale group, which shows variability on timescales longer than a year. The case against such long-term variability is made by Rigon et al (2017) and Venuti et al (2015). The former carry out a similar analysis to ours using "pooled sigma" which is broadly equivalent to the SF, for a sample of 39 Class II stars for timescales longer than a week.…”
Section: The Variability Of Class II Ysos For τ >1 Yearmentioning
confidence: 91%
“…Simonetti et al 1985;Hughes et al 1992;de Vries et al 2003). Its use for characterising young stars has been more limited, with Rigon et al (2017) using the closely related "pooled sigma" for a sample of bright objects and assessing the usefulness of the related ∆m-∆t plots.…”
Section: Introductionmentioning
confidence: 99%